TATBIQ NAMUDHAJ TUEALIM MAKE A MATCH FI TAHSIN NATAYIJ TAEALUM TAMRINAT ALEARABIA FI ALSAFI ALTAKHASUS A LILBANAT FI ALMADRASAT ALEALIA JAMIEAT 'UMI ALQURAA AL'IISLAMIU BUGHUR - Nuraeni, Erni; Fahmi, Nurul (Program Studi Pendidikan Bahasa Arab, 2025)
This research is based on the fact that learning at the madrasah aliyah level often faces various challenges, especially related to student activity and participation in the learning process. Obstacles that are often encountered include monotonous learning methods, lack of interaction between teachers and students, and low student motivation to learn. This research aims to increase student activity and participation in learning Arabic, as well as improve student learning achievement through the application of the Make a Match learning model on Tamrin Arabic material. The method used is Classroom Action Research (PTK) with a quantitative approach which is carried out in two learning cycles The results showed a significant improvement in the cognitive aspect, where the average class score increased from 73.6 with a completion rate of 72% in the first cycle, to 96.95 with 100% perfect completion in the second cycle. The conclusion of this study proves that the Make a Match model is an effective method to improve the quality of Arabic language learning, not only in terms of active participation of students but also in improving understanding and mastery of learning materials. This learning model has succeeded in creating a more dynamic and interactive learning atmosphere, as well as having a transformative impact on the quality of Arabic language learning at the madrasah aliyah level